2015
DOI: 10.1556/036.102.2015.4.12
|View full text |Cite
|
Sign up to set email alerts
|

ACE and ACTN3 genes polymorphisms among female Hungarian athletes in the aspect of sport disciplines

Abstract: The aim of the study was to determine the importance of two sport-associated gene polymorphisms, alpha-actinin-3 R577X (ACTN3) and angiotensin-converting enzyme I/D (ACE), among Hungarian athletes in different sports. The examination was carried out only on women (n = 100). Sport-specific groups were formed in order to guarantee the most homogeneous clusters. Human genomic DNA was isolated from blood, and genotyping was performed by polymerase chain reaction. To measure the differences between the participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…A previous study found that there were significant differences in the peak heart rate of the RR genotype and RX genotype in the male group but no significant differences in the female group, and high values of all endurance indexes appeared in the female group with the XX homozygous genotype ( Deschamps et al, 2015 ). Similarly, in this study, the 577X allele was not significantly associated with any traits of female athletes, consistent with the results of excellent endurance-oriented athletes such as Italian rowers ( Paparini et al, 2007 ), Russian rowers ( Weyerstraß et al, 2018 ), and Hungarian rowers ( Bosnyák et al, 2015 ). This could be explained by the fact that rowing is a complex discipline with a vigorous power-start demanding starting anaerobic capacity, an immediately high aerobic steady state, and an extremely exhausting spurt.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study found that there were significant differences in the peak heart rate of the RR genotype and RX genotype in the male group but no significant differences in the female group, and high values of all endurance indexes appeared in the female group with the XX homozygous genotype ( Deschamps et al, 2015 ). Similarly, in this study, the 577X allele was not significantly associated with any traits of female athletes, consistent with the results of excellent endurance-oriented athletes such as Italian rowers ( Paparini et al, 2007 ), Russian rowers ( Weyerstraß et al, 2018 ), and Hungarian rowers ( Bosnyák et al, 2015 ). This could be explained by the fact that rowing is a complex discipline with a vigorous power-start demanding starting anaerobic capacity, an immediately high aerobic steady state, and an extremely exhausting spurt.…”
Section: Discussionsupporting
confidence: 90%
“…the foregoing reflects that the risk of injury prevails over the individual who does not manifest it. This is how Miyamoto et al [45] infer that this polymorphism is responsible for changes in the sarcomeric cytoskeleton leading to muscle stiffness and prevalence of injury [46]. One of the limitations found in this study was the diversity of polymorphisms associated with sports injuries as well as the limited availability of research on a gene or a defined polymorphism.…”
Section: Discussionmentioning
confidence: 80%
“…The Hungarian endurance group also contained rowers ( n = 32 out of N = 110) that may have contributed to these results. Furthermore, the similarity of the Hungarian athletes's genetic background with the Polish population has already been described with other gene variants (Bosnyák et al., 2015). The higher representation of Ser allele (compared to Pro allele frequency and the alleles to the control group) was not discoverable in the power group, so this research cannot strengthen the association of the muscle activity and the Ser allele that was reported before (Ahmetov et al., 2008; Cięszczyk et al., 2011, 2012).…”
Section: Discussionmentioning
confidence: 81%